Studies on the Enhancement of Chebulinic Acid Using the Composition of Medicinal Herbs by Baker’s Yeast - Prakash, D.V. Surya; Vangalapati, Meena (International Journal of Applied Sciences and Biotechnology, 2015)
Chebulinic acid is a phenolic compound, commonly found in the Terminalia chebula, Phyllanthus emblica, Dimocarpus longan species etc. The enhancement of Chebulinic acid was obtained from the composition of medicinal herbs by using Baker’s yeast (Saccharomyces cerevisiae) under fermentation process. The optimum results were observed for the effect of % inoculum, substrate wt, incubation period, temperature, pH, carbon sources and nitrogen sources were 2.0ml, 6g, 48hr, 30oC, 4.0, sucrose and yeast extract respectively. The Chebulinic acid concentration enhanced from 3.4 to 6.8mg/ml for the optimised conditions. Int J Appl Sci Biotechnol, Vol 3(3): 439-442